Synthesis, Characterization, DFT Calculation, Photochromic, Antimicrobial and Antifungal Properties of Co(II), Ni(II), Zn(II), Ag(I) Complexes with Azo Dye of 2-Aminopyrimidine - Yareeb Jwad Sahar (Journal of Global Pharma Technology, 2016)
A New azo dye 3-(2-pyrimidinylazo)-4-dimethylbenzaldehyde (PADB) consisting 2-aminopyrimidine was synthesized by coupling reaction of diazonium salt and 4-dimethylaminobenzaldehyde. The PADB was further utilized to synthesis of its complexes with Ni (II), Co (II), Zn (II) and Ag (I). All the synthesized complexes were characterized by different techniques (infrared, UV-VIS and mass spectroscopies and elemental analysis). The complexes of Co (II) and Ni (II) were found to be octahedral and nonelectrolytic with general formulas [M (PADB)2 Cl2]. The complexes of Zn (II) and Ag (I) were tetrahedral and electrolytic with general formulas [Zn (PADB) Cl2] and [Ag (PADB) (H2O)] NO3 which iselectrolytic. The PADB and its complexes exhibited potent antimicrobial activities against two types of bacterial strains, Staph-aureus (positive gram) and E-coli (negative gram) and two types of fungies: Aspergillus niger and Pinicillium-Sp. The PADB dye exhibited good phtochromic and solvachromic properties.Keywords: Pyrimidine, Photoisomerization, Pyrimidinylazo, Biological activity, Inorganic chemistry.